Sex-specific association between body mass index and cerebral microbleed progression in adults aged 50–85 years - Yoon, Cindy W.; Suh, Young Ju; Kim, Byeong C.; Youn, Young Chul; Jeong, Jee Hyang; Choi, Seong Hye (Frontiers in Neurology, 2025)
Background and purposePrevious studies have demonstrated sex differences in the association between body mass index (BMI) and hemorrhagic stroke. Cerebral microbleed (CMB) is a clinically important marker of bleeding-prone microangiopathy, which is associated with a risk of hemorrhagic stroke. No study has evaluated sex differences in the relationship between BMI and CMB. In this longitudinal study, we aimed to conduct sex-stratified analyses to assess whether sex modifies the effect of BMI on CMB progression.MethodsThe database of the CHALLENGE study (Comparison Study of Cilostazol and Aspirin on Changes in Volume of Cerebral Small Vessel Disease White Matter Changes), which enrolled patients aged 50–85 years with cerebral small vessel disease, was analyzed. Of the 256 subjects, 189 who underwent a 2-year follow-up brain MRI scan were included in the analysis. We used a generalized linear mixed model with a negative binomial distribution to assess the association between BMI and the 2-year change in CMB count, and conducted sex-stratified analyses to account for potential sex-specific effects.ResultsA total of 65 men and 124 women were analyzed. In the sex-stratified negative binomial model, a significant association was observed in women but not in men. In women, each 1 kg/m2 increase in BMI was significantly associated with a decrease in the 2-year change in the number of total CMBs after adjustment for age and baseline CMB count [β = −0.120, 95% confidence interval (CI): −0.202 to −0.037, p = 0.005]. When CMBs were categorized into lobar and deep/infratentorial regions, significant associations were observed for both lobar (β = −0.114, 95% CI: −0.213 to −0.015, p = 0.024) and deep/infratentorial CMBs (β = −0.123, 95% CI: −0.222 to −0.023, p = 0.015). By contrast, no significant associations were identified between BMI and the 2-year change in CMB counts in men (all p > 0.05).ConclusionHigher BMI in later life was associated with less progression of CMBs in women, but not in men.